Tertullian and Montanism: Ancient Sabbath and its implications for Pentecostalism - Pakpahan, Gernaida K. R.; Hasiholan, Anggi M. (Verbum et ecclesia, 2024)
The Sabbath is widely observed differently among Christians, including Pentecostals. Different interpretations of the Sabbath cause this difference. According to Pentecostals, it is necessary to trace the history of the ancient Church to find the meaning of the Sabbath. This article explores Tertullian’s thoughts on the Sabbath before and after joining Montanism. The research method used in this article is descriptive qualitative with a historical approach. The research results show significant differences in Tertullian’s understanding of the Sabbath before and after joining Montanism. Montanism changed Tertullian’s view of the Sabbath in the context of respect and the essence of honouring the Sabbath. However, both of Tertullian’s understandings have contributed to the Pentecostal understanding of the Sabbath. Pentecostals understand the Sabbath as a relationship with Christ that leads to eternity because it has eschatological meaning. Towards eternity, it must be maintained while still in the world. Honouring the Sabbath changed from the seventh day to the eighth day because it aims to celebrate the Resurrection of Jesus.Intradisciplinary and interdisciplinary implicationsThe Sabbath is a time of rest and joy associated with Jesus’s Resurrection. The concept of the Sabbath originates from Tertullian’s thoughts before and after joining Montanism, which provides a broad dimension to the theme of the Sabbath in Creation theology. This research has implications for studying the history of Christianity and the concept of the Sabbath in the Pentecostal Church in Indonesia.